Patterns and causes of deviations in English verbal inflectional suffixes among Thai ELF learners - Napasri Timyam, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study investigates the use of three verbal inflectional suffixes, i.e., the present tense -s, the past tense -ed, and the progressive -ing, among Thai ELF learners. It examines how they deviate from ENL norms and the causes of deviations are analysed. Data were taken from the academic writing of 116 English-major students at a university in Bangkok. The results showed that Thai ELF learners who have advanced and upper-intermediate level English knowledge and skills have acquired the ability to use these three suffixes, but they sometimes deviate from ENL norms. They tend to omit the -s ending when there is a long distance between the main subject and main verb, when there is a heavy subject containing a head and pre-/post-modifiers, and when the subject appears as a structurally complex category. They often omit the -ed ending when there are several past tense verbs in a sentence. They extend the use of the progressive aspect to talk about a general truth or habit which is typically expressed by the present simple tense in ENL. Results suggest that linguistic and functional causes are responsible for these deviations. Thai ELF learners use the zero forms of present and past tense verbs as a result of both syntactic complexity and the pragmatic motives of the efficiency of communication as well as the exploitation of redundancy. They use progressive verbs with general truths or habits due to the attractive form and meaning of this aspect and also the pragmatic motive of added prominence.